Comparative evaluation of the efficacy of three commercially available toothpastes on dentin hypersensitivity reduction: an 8-week clinical study - Swathi Venkataramana; Selva Kumar Jeyaraman; Sai Sarath Kumar Kothimbakkam; Burnice Nalina Kumari Chellathurai (Wolters Kluwer Medknow Publications, 2020)
Objective: The objective of this 8-week, single-center, double-blind, three-cell, randomized, clinical study was to compare the efficacy in reducing the dentin hypersensitivity of three commercially available toothpaste: Group A toothpaste containing 8.0% arginine, calcium carbonate, and 1450 ppm fluoride as sodium monofluorophosphate; Group B toothpaste containing 8% strontium acetate and 1040 ppm fluoride as sodium fluoride; and Group C toothpaste containing 5% potassium nitrate and 917 ppm fluoride as sodium monofluorophosphate. Materials and Methods: One hundred and fifty subjects, who reported to the department having teeth sensitive to tactile and air blast hypersensitivity, were assigned to one of the three study groups (50/group). Subjects were then asked to brush their teeth for 1 min, twice daily, with the given toothpaste. The dentin hypersensitivity of the two selected teeth was evaluated at baseline, 2 weeks, 4 weeks, and 8 weeks. Comparison of the treatment groups was conducted using the VAS analysis. Results: All 150 subjects complied with the protocol and completed the 8-week clinical study; there were no adverse events on the soft or hard tissues of the oral cavity. Group A resulted in more improvement in the reduction of sensitivity at 2, 4, and 8 weeks compared to the other groups. Conclusions: Group A toothpaste containing 8.0% arginine, calcium carbonate, and 1450 ppm fluoride as sodium monofluorophosphate significantly reduces dentin hypersensitivity and more effective than Group B and Group C toothpaste. Group A toothpaste is the latest new tool in the armament of the modern dentist.